A new densification mechanism of copper powder sintered under an electrical field. (1st April 2015) - Huang, Kunlan; Yang, Yi; Qin, Yi; Yang, Gang; Yin, Deqiang
Abstract : A new sintering mechanism is revealed for copper powder sintered under the influence of an electrical field and a force field during the formation of microcomponents. Analysis of the microstructure and grain boundary evolution of the sintered samples showed that the disappearance of the interface at contact areas between particles is a continuous process which involves new grain formation and grain refinement during this innovative microsintering process. The densification process is therefore different from what is known in a conventional powder sintering process.